Integrating sustainability into corporate strategy: a case study of the textile and clothing industry - Peters, J.; Simaens, A. (Sustainability, 2020)
This paper aims to explore a set of institutional, organizational, and individual drivers of and barriers to the integration of sustainability into the corporate strategy of a European textile and clothing (T&C) company. The methodology is based on a case study of the exemplar VAUDE, a family-owned sustainable outdoor outfitter company. The results are in accordance with institutional theory and stakeholder theory as a theoretical framework explaining why companies deal with sustainability. The determined drivers depend on coherence at all levels of analysis, i.e., institutional, organizational, and individual. The barriers found are of an institutional and organizational nature only. The findings present significant practical implications for other T&C companies that seek to integrate sustainability into their corporate strategy and for the T&C industry to create a sustainability-friendly environment to drive more companies to become sustainable. It further supports T&C companies in identifying potential barriers, determining how to overcome them, and successfully integrating sustainability into their corporate strategy. To conclude, the results suggest that it only works if sustainability is strongly integrated into the corporate strategy and deeply anchored in all departments and daily tasks of a T&C company.